PERSONAL DATA PROTECTION IN FALSIFICATION OF COVID-19 VACCINATION CERTIFICATES: A JURIDICAL VIEW - Abdul Razak, Muhammad; Novita, Rissa Dwi (YURIS: Journal of Court and Justice, 2022)
The obligation to show a Covid-19 vaccination card in a public place has its advantages and disadvantages. Some parties support it for the purpose of protecting the public interest, while others are questioning it because of the unequal vaccinations distribution in various regions. In addition, the need to show Covid-19 vaccination card to public through Peduli Lindungi application raises legal issues such as vulnerability to misuse of personal data and criminal activities. This research aims to know the legal regulation from government and ministry regarding the criminal case of misused personal data and falsificate Covid-19 vaccine certificates for their own profit. The research method used is normative method. The normative juridical research method is library law research which is conducted by examining library materials or secondary data. The research is used statutory approach that intended to understand and comprehensively analyze the hierarchy of laws, regulations and its principles. The civil law of government provisions regarding fake vaccine certificates circulation have been regulated, because there are many circulating fake vaccine certificates for Covid-19. The regulation also includes sanctions that will be given to perpetrators who falsify the Covid-19 vaccine certificates.